Legal Certainty Against The Signing of Deeds That Are Not Made in The Presence of A Notary Public - Pane, Musa Darwin; Arline, Lidya De Vega (Manunggal Halim Jaya, 2025)
A notary is a public official authorised to draw up authentic deeds and process legal documents, such as letters of agreement, deeds of sale, and other important documents with legal force. Although signed by the parties, the documents drawn up by a notary are not treated as authentic documents and have only the force of private writing (Article 1869 of the Civil Code). The definition of an authentic deed is contained in Article 1868 of the Civil Code, which states that an authentic deed is a deed drawn up in a form prescribed by law, by or in the presence of public officials authorised to do so, in the place where the deed is drawn up. The Notaries Act requires notaries to read documents in the presence of the parties. Article 16(7) UUJN regulates the obligation of notaries to read documents in front of the parties. A deed not read in front of the parties may become private, lose its evidential force, and be considered null and void.